Hubungan Menonton Video Youtube Dengan Kemampuan Komunikasi Anak Usia 5 -6 Tahun - Kristiana Maryani; Siti Khosiah; Siti Amaliah (UIN Sultan Maulana Hasanudin Banten, 2022)
Communication is a variety of opinions and emotions. Communication is used by: code, reaction, verbal and nonverbal, but communication is very familiar in the form of speech. The media that children are most interested in is YouTube, usually YouTube videos are made up of mixture of pictures and songs that children like the most. This study aims to determine wheter there is a relationship between watching YouTube videos and the communication skills of children aged 5-6 years in Ketileng Village, Cilegon District, Cilegon City-Banten. The method used in this study is quantitative correlation, sampling using purposive sampling with a sample of 46 children in early childhood education institutions Ketileng Village. The results of this study indicate that thevalueofsig(2-tailed) is 0.001<0.005, so it can be concluded that there is a relationship between watching YouTube videos and the communication skills of children aged 5-6 years in Ketileng Village, Cilegon District, Cilegon City-Banten. With a correlation value of 0.0469 means that it has a stong relationship watching YouTube videos with the communication skills of children aged 5-6 years.